The effect of infection with soybean mosaic virus on the growth and formation of bacterial nodules of soybean plants (Journal of the College of Basic Education, 2022)
The results of the study indicated that infection with soybean mosaicism led to a significant reduction in the number and weight of bacterial nodules, in addition to a reduction in the dry weight of the seeds. The percentages of reduction were calculated on the basis of the comparison treatment.